Pengaruh Kreativitas Periklanan Terhadap Keputusan Pembelian pada Konsumen Starbucks Coffee di Bandara Internasional Sultan Hasanuddin Makassar - Wendy Wendy Souisa (Sekolah Tinggi Ilmu Ekonomi (STIE) Tri Dharma Nusantara Makassar, 2021)
This study aims to determine the effect of attention, interest, desire and action advertising variables on consumer purchasing decisions for Starbucks Coffee at Sultan Hasanuddin International Airport Makassar. From this study, it was found that there was a significant effect of attention, interest, desire and action advertising variables on consumer purchasing decisions for Starbucks Coffee at Sultan Hasanuddin International Airport Makassar, and the regression equation was obtained: Y = 4,475 + 0,439 (X1) + 0,185 (X2) + 0,409 (X3) + 0,134 (X4). From the equation above, it can be seen that the attention variable has a greater influence when compared to other variables. The importance of consumer assessment of product purchase decisions through advertising must be a concern for the company, therefore it is necessary to further improve the creativity and quality of advertising messages in an effort to obtain good ratings from consumers.